2003
DOI: 10.1017/s1092852900006945
|View full text |Cite
|
Sign up to set email alerts
|

WCA Recommendations for the Long-Term Treatment of Generalized Anxiety Disorder

Abstract: What are the current recommendations for the long-term treatment of generalized anxiety disorder (GAD)? GAD is a common disorder with a lifetime prevalence of 4% to 7% in the general population. GAD is characterized by excessive, uncontrollable worry or anxiety about a number of events or activities that the individual experiences on more days than not over a 6-month period. Onset of GAD symptoms usually occurs during an individual's early twenties; however, high rates of GAD have also been seen in children an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 41 publications
1
40
0
5
Order By: Relevance
“…The most widely used therapeutic agents for the treatment of anxiety disorders include selective serotonin reuptake inhibitors, serotonin and norepinephrine reuptake inhibitors, benzodiazepine anxiolytic and NMDA receptor modulators [5] . However, currently available anxiety disorder modulators are inadequate for patients because of the existence of "nonresponders" or unwanted side effects, such as ataxia, drowsiness, and impairment of cognition [6][7][8] . Increasing evidence indicates that the dynorphin/κ opioid receptor system plays an important role in the regulation of anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used therapeutic agents for the treatment of anxiety disorders include selective serotonin reuptake inhibitors, serotonin and norepinephrine reuptake inhibitors, benzodiazepine anxiolytic and NMDA receptor modulators [5] . However, currently available anxiety disorder modulators are inadequate for patients because of the existence of "nonresponders" or unwanted side effects, such as ataxia, drowsiness, and impairment of cognition [6][7][8] . Increasing evidence indicates that the dynorphin/κ opioid receptor system plays an important role in the regulation of anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…26 Furthermore, there is no data that indicate an accumulation of adverse events; e.g. getting Alzheimer or cancer.…”
Section: -25mentioning
confidence: 99%
“…Although not as widely prescribed as in the past, these compounds nevertheless remain an effective alternative to SSRIs. That said, the nonselective BZDs are not devoid of side effects, which can include drowsiness, ataxia, impairment of cognition, as well as the risk of dependence and withdrawal symptoms, including increased anxiety, tremors, and seizures (Noyes et al, 1988;Bennett et al, 1998;Yamawaki, 1999;Allgulander et al, 2003). The identification of subtype-selective GABA receptor-positive allosteric modulators, such as zolpidem, which have proven to be effective in the treatment of patients with insomnia while producing fewer untoward side effects than nonselective BZDs, suggested that similar drugs could be developed for anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%